Celtomachia apud Pydnam? Nude Warriors in the Frieze of the Pillar of L. Aemilius Paullus at Delphi - Reimann, Lukas (Römische Mitteilungen, 2022)
Among the Roman and Macedonian combatants peopling the battle frieze of the pillar of L. Aemilius Paullus at Delphi, three nude figures fighting on the losing side can be identified as Celts. As Celtic mercenaries played a negligible role in the battle at Pydna, this article holds that the Celtomachic motifs were included deliberately as an opportune pictorial code to represent and qualify the Aemilian victory to a panhellenic audience. The three Celts specifically answered to the barbaricising Attalid and Roman pre-war propaganda, aimed at the denigration of popular king Perseus, while countering wide-spread anti-Roman sentiment, in kind revolving around the topos of barbarism.